Anthropogenic Pollution Assessment of Pertek (Tunceli) Geothermal Field - Balaban, Tugbanur Ozen; Okan, Ozlem Oztekin; Sancar, Taylan; Onal, Ayten Oztufekci (Tmmob Jeoloji Muhendisleri Odasi, 2020)
The study area is located in Pertek town in Tunceli province in Eastern Anatolia. The geology of the study area is very important for the geodynamic evolution of the Eastern Taurus. Geological formations in the study area are Paleozoic Keban metamorphics, Upper Cretaceous Harami Formation, Middle-Upper Eocene Kirkgecit Formation, Upper Miocene Karabakir Formation, and Quaternary alluvium, from the oldest to the youngest, respectively. Hydrogeological units were divided into three units in accordance with lithological, structural and hydrogeological properties. The basement of the study area of sandstone, marbles and dolomitic marbles in the Keban metamorphic rocks are highly fractured and karstified and act as the main reservoir in particular for thermal waters in the study area. Kirkgecit and Karabakir Formations occur as barrier rocks in the geothermal area due to impermeable properties. Some levels of limestone units within the Keban metamorphics are aquifers for freshwater. Alluvium is the most important and suitable unit for cold groundwater production. In the study area, streams and rivers flow from southwest to northeast towards Keban Dam Lake. The lake is very important in the region from the point of view of hydroelectric power production, flood control, and irrigation. The thermal and mineral waters generally have high mineral contents. When they are discharged onto the surface, they can cause contamination in surface water, ground water, and of soil. Because of the fact that the water resources in the region are used for drinking and irrigation purposes, the quality of the water is evaluated within the scope of this study. For this reason, water and sediment samples were analyzed for boron, arsenic and other contaminant (Pb, Fe, Sb, Sn and Hg) substances to measure the contamination. The results acquired from the analysis of water samples suggest that concentrations of B, As and Pb in some of the samples exceed the limits of the TSE drinking-water standards(>100 ppb). Fe concentration is 2.16 ppm, Hg and Sb concentrations are also 0.05 ppm. Moreover, some of the sediment samples collected from thermal springs in Singec Creek are contaminated with B, As, Sb, Hg and Pb and other elements sourced from geothermal fluids. In this study, the geochemical evaluation of the presence of B, As, and other contaminants (Pb, Fe, Sb, Sn) derived from geothermal activities within sediment and water in the Pertek Geothermal Field and surrounding area were discussed.
Keywords: Pertek; geothermal; hydrogeochemistry; anthropogenic pollution